2017
DOI: 10.1088/1748-9326/aa6e8a
|View full text |Cite
|
Sign up to set email alerts
|

Will the use of a carbon tax for revenue generation produce an incentive to continue carbon emissions?

Abstract: Integrated assessment models are commonly used to generate optimal carbon prices based on an objective function that maximizes social welfare. Such models typically project an initially low carbon price that increases with time. This framework does not reflect the incentives of decision makers who are responsible for generating tax revenue. If a rising carbon price is to result in near-zero emissions, it must ultimately result in near-zero carbon tax revenue. That means that at some point, policy makers will b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Signatory countries to the Paris Climate Agreement have committed to undertake actions to reduce and eventually halt carbon dioxide (CO 2 ) emissions on a specified time schedule. 1,2 Actions contemplated include instituting carbon prices. 3 Carbon prices increase costs of energy consumption and it has been suggested that the increased costs induce more rapid technological change.…”
Section: Introductionmentioning
confidence: 99%
“…Signatory countries to the Paris Climate Agreement have committed to undertake actions to reduce and eventually halt carbon dioxide (CO 2 ) emissions on a specified time schedule. 1,2 Actions contemplated include instituting carbon prices. 3 Carbon prices increase costs of energy consumption and it has been suggested that the increased costs induce more rapid technological change.…”
Section: Introductionmentioning
confidence: 99%
“… 30 However, concerns remain regarding revenue instability and perverse incentives for emission reduction in the longer term. 31 …”
Section: Taxes and Microleviesmentioning
confidence: 99%
“…Similarly, carbon markets may pay cash to increase social welfare while giving financial incentives to minimize carbon emissions (Spaargaren & Mol, 2013). To be explicit, carbon exchanges are not intended to eliminate carbon emissions; instead, they are intended to lower emissions by discouraging their usage and financially compensating firms and industries that rely substantially on carbon-intensive operations (Wang et al, 2017). To summarize, DS is not a cure for our planet's environmental problems.…”
Section: Debilitated Sustainabilitymentioning
confidence: 99%